TESTING CHEMICAL ZINC PHOSPHATE BASE AS A CORROSION INHIBITOR ON CARBON STEEL IN THE CORROSION MEDIA OF COOLING WATER, SEA WATER AND PDAM WATER - Sariadi, S; Kenady, Rengga Rahmat; Irwan, I; Zaini, Halim (Politeknik Negeri Lhokseumawe, 2024)
ABSTRACT Zinc phosphate base corrosion inhibitor which aims to determine the effectiveness of the inhibitor to provide protection to carbon steel against the rate of corrosion, with variations in inhibitor concentration at 0, 20, 40 and 60 ppm.This research uses the weight loss method and studies the performance of zinc phosphate base chemical inhibitors in the mediacooling water, sea water and PDAM waterThis is done by carrying out SEM (Scanning Electron Microscopy) testing. The type of steel specimen used in the research is Carbon Steel and deepCorrosion media are cooling water, sea water and PDAM water.The addition of zinc phosphate base carbon steel inhibitor is effective in reducing the corrosion rate of carbon steel in PDAM water and sea water. in sea water media without inhibitors, a drastic reduction in the corrosion rate was seen from 119.0457 mpy to 1.7754 mpy and in PDAM water media without inhibitors, a drastic decrease in the corrosion rate was seen from 18.5873 mpy to 3.4163 mpy, after adding inhibitors with a concentration of 60 ppm. The efficiency of the zinc phosphate base inhibitor in cooling water corrosion media was 30.262% at a concentration of 40 ppm and a soaking time of 20 days.Keywords : Inhibition efficiency, Corrosion Inhibitors, Corrosion in sea water, Corrosion in cooling water, Corrosion Rate, Zinc Phosphate base.